THE DEVELOPMENT OF EMBEDDED ROBOTIC TRAINING KIT USING RASPBERRY PI FOR BEGINNERS IN STEM EDUCATION WITHIN TVET FRAMEWORK - MOHD FIRDAUS BIN MOHD REJAB; FADLILHISHAM BIN AHMAD, (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
In the era of the Fourth Industrial Revolution (IR 4.0), the demand for practical and industry-relevant STEM education has grown significantly. This project addressed this need by developing an embedded robotic training kit using Raspberry Pi, which offers an accessible and practical tool for beginners in STEM education and is designed within the framework of technical and vocational education and training (TVET). This kit integrates essential components such as LEDs, buzzers, ultrasonic sensors, and Pi cameras, offering hands-on learning experiences in robotics and embedded systems. Powered by the versatile Raspberry Pi, the kit utilizes Python programming and the Thonny IDE to simplify coding for beginners while encouraging project-based learning to foster creativity and innovation. The project integrates theoretical knowledge with practical application, fostering critical problem-solving skills and preparing students for modern technological demands. By aligning with TVET objectives, the training kit enhances employability by developing essential, industry-relevant competencies.